Application of online marketing techniques and concepts to develop the social media marketing strategy for Impact Hub Dhaka - Mahtab, Tanvir (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.